2019
DOI: 10.2478/bsrj-2019-0013
|View full text |Cite
|
Sign up to set email alerts
|

Health Technology Assessment: The Role of Total Cost of Ownership

Abstract: Background: Recently the European Union, through its Horizon 2020 fund has awarded numerous research projects tasked with the development of cloud-based health technology solutions. A number of these projects have a specific focus on ambient assisted living (AAL) technologies; solutions that offer a unique opportunity to improve the quality of life of persons with mild cognitive impairments. The diffusion of these solutions across a European wide cloud infrastructure presents a novel opportunity to reduce econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Traditional HISs usually suffer from lack of uniform standards for data-sharing, medical records management problems, high cost of developing independent construction and system upgrade and maintenance issues (Kanagaraj and Sumathi, 2011; Lian et al , 2014; Setareh et al , 2014; Tahmasbi et al , 2016; Meri et al , 2019). As compared to traditional HISs, cloud-based HISs can enable users not only to store, manage and retrieve medical-related data via offering a flexible, scalable and low-cost solution, but also to monitor patients’ health conditions via providing a reliable, secure and accessible way on the cloud, from anywhere, at any time, with any device, by logging in on a dedicated page (Low and Chen, 2012; Lian et al , 2014; Jia et al , 2018; McConalogue et al , 2019; Meri et al , 2019; Xu et al , 2019). This is the reason why some hospitals have implemented cloud-based HISs to enable their professionals to access, save, retrieve, and share all kinds of clinical information from anywhere and at any time with unlimited storage space.…”
Section: Theoretical Background Hypotheses and Research Modelmentioning
confidence: 99%
“…Traditional HISs usually suffer from lack of uniform standards for data-sharing, medical records management problems, high cost of developing independent construction and system upgrade and maintenance issues (Kanagaraj and Sumathi, 2011; Lian et al , 2014; Setareh et al , 2014; Tahmasbi et al , 2016; Meri et al , 2019). As compared to traditional HISs, cloud-based HISs can enable users not only to store, manage and retrieve medical-related data via offering a flexible, scalable and low-cost solution, but also to monitor patients’ health conditions via providing a reliable, secure and accessible way on the cloud, from anywhere, at any time, with any device, by logging in on a dedicated page (Low and Chen, 2012; Lian et al , 2014; Jia et al , 2018; McConalogue et al , 2019; Meri et al , 2019; Xu et al , 2019). This is the reason why some hospitals have implemented cloud-based HISs to enable their professionals to access, save, retrieve, and share all kinds of clinical information from anywhere and at any time with unlimited storage space.…”
Section: Theoretical Background Hypotheses and Research Modelmentioning
confidence: 99%
“…Hence, understanding and establishing common goals for this particular performance measure can prove to be difficult. Similarly McConalogue et al (2019) study indicated that advancing technologies benefits are evident despite the challenges especially for suppliers in terms of cost associated with initial set up, maintenance and learning.…”
Section: Assessing Suppliers’ Performancementioning
confidence: 95%
“…Delivery cost Kaplan & Norton (1992, 19962004) Supplier integration; standardisation of performance measures Guiffrida and Nagi (2006) Short-long term financial performance Gunasekaran et al (2001) Akamp and Muller (2013) Supplier management Kaplan & Norton (1992, 19962004) Supplier integration; standardisation of performance measures Gunasekaran et al (2001) Supplier-buyer communication Bukh & Malmi (2005) Customer satisfaction and customer profitability Bhagwat & Sharma (2007) Supplier development; Cagliano et al (2014) Capacity utilisation; communication Krause et al (2000) Continuous improvement; communication Mani et al (2018) Capacity utilisation Advancing technologies (ADT) Kaplan & Norton (1992, 19962004) Supplier integration; standardisation of performance measures Gunasekaran et al (2001) Supplier development Bak (2016) Supply chain integration Bukh & Malmi (2005) Customer satisfaction and customer profitability Bhagwat & Sharma (2007) Supplier development Cagliano et al (2014) Logistics performance Gordon (2008) Supply chain visibility McConalogue, et al (2019).…”
Section: Literature Contextmentioning
confidence: 99%
See 1 more Smart Citation